(untitled) (Revista científica Olimpia, 2020)
As in other sports modalities, the practice surface plays an important role both for the development of the sport itself and for the influence of the number and type of injuries, thus with the present study it is intended to know the type of injuries based on the surface used during Karate workouts. 515 karatekas from all over Spain were analyzed. Participants filled in a questionnaire consisting of 4 sections: information about the subject, injuries related to the practice surface, injuries related to the tatami and other contributions. 92% of the respondents stated that they have suffered some type of injury attributed to the practice surface. The injuries that have occurred most related to the surface have been: blisters on the soles of the feet, chafing and muscle overloads. Of these three injuries, the training surface that causes more blisters on the foot is the canvas, the one that causes more chafing is the non-approved karate tatami, and the one that causes more muscle overload is the synthetic floor.